On some generalized difference sequences of fuzzy numbers - Altin, Yavuz; Et, Mikail; Basarir, Metin (Academic Publication Council, 2007)
The purpose of this paper is to introduce the concepts of statistical convergence and strongly (p)-Cesaro convergence of generalized difference sequences of fuzzy numbers. We give some relations related to these concepts. We show that Delta(m)-statistical convergence and strongly (p)-Cesaro convergence are equivalent for Delta(m)-bounded sequences of fuzzy numbers. We also introduce the concept of Delta(m)-statistically Cauchy sequence and show that it is equivalent to Delta(m)-statistical convergence.
Keywords: difference sequences; fuzzy numbers; statistical convergence